2015
DOI: 10.1007/s00384-015-2272-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oncologic outcomes of metastatic rectal cancer patients with or without neoadjuvant chemoradiotherapy

Abstract: Neoadjuvant chemoradiotherapy may not affect local control and overall survival in locally advanced rectal cancer with distant metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
(33 reference statements)
0
6
0
1
Order By: Relevance
“…Six studies compared the OS of patients with RC treated with Neo-CT vs Neo-CRT. Sun et al [ 19 ] and Cassidy et al [ 20 ] reported that Neo-CRT improved OS, while Deng et al [ 10 ], He et al [ 27 ], Fan et al [ 13 ], and Kim et al [ 21 ] reported no benefit. After merging all studies, Neo-CRT did not improve OS [HR = 1.09, 95% confidence interval (CI) = 0.93–1.24; p = 0.19] (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies compared the OS of patients with RC treated with Neo-CT vs Neo-CRT. Sun et al [ 19 ] and Cassidy et al [ 20 ] reported that Neo-CRT improved OS, while Deng et al [ 10 ], He et al [ 27 ], Fan et al [ 13 ], and Kim et al [ 21 ] reported no benefit. After merging all studies, Neo-CRT did not improve OS [HR = 1.09, 95% confidence interval (CI) = 0.93–1.24; p = 0.19] (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent study included rectal carcinoma patients with synchronous metastases who received combination of FOLFOX chemotherapy with split-course pelvic chemoradiation (FOLFOX + CRT) and obtained median overall survival of 23 months [32]. Another study compared outcomes of neoadjuvant chemoradiotherapy and postoperative systemic chemotherapy without radiotherapy in metastatic rectal cancer patients and achieved 24 and 27 months of median overall survival, respectively [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, survival benefit was not observed in the two independent studies. On the contrary, Kim et al 13 evaluated the oncological effects of neoadjuvant radiotherapy versus pure postoperative chemotherapy in 86 patients with rectal cancer and synchronous liver metastasis receiving TME procedure and found that neoadjuvant chemoradiotherapy did not improve local control and overall survival. The local recurrence rates were 10% in neoadjuvant chemoradiotherapy group and 15.2% in postoperative systemic chemotherapy without radiotherapy group and did not reach a significant difference.…”
Section: Discussionmentioning
confidence: 99%